Menakar “Gen” Hukum Indonesia Sebagai Dasar Pembangunan Hukum Nasional - Isdiyanto, Ilham Yuli (Jurnal Hukum & Pembangunan, 2018)
This research takes a new term called “legal gene” to explain the historical map hereditary about legal model in Indonesia. The legal gene thinking method then combined with historical-normative method so that the prescriptive element can be obtained as the final result from this research. The final result concluded that the study of legal gene in Indonesia is still far from perfect, especially legal gene study which more systematic and comprehensive since kingdom period, colonial, until Indonesian Republic period. Things get more severe because the Government seems not serious taking this matter, thus the aftermath is the discourse and national legal development efforts always spinning around and not comprehensive. Furthermore, Common Law as the wealth of the nation often ignored even though Common Law is a good legal gene as a foundation to developing National Law. As an advice, Government needs to do more serious, systematic, and comprehensive efforts to conduct research and studies about legal gene in Indonesia thus becoming the main ingredient for national legal development. This is more urgent when Indonesia also entered the fourth industrial revolution / Industry 4.0.